Computed tomography features of Stenotrophomonas maltophilia pneumonia in patients with neutropenic fever: report of two cases - Kan Kassel, Tsang Wai; Lok Ryan, Lee Ka; Li, Allen (Multidisciplinary Respiratory Medicine, 2013)
Stenotrophomonas maltophilia (S. maltophilia) is a rare yet important global emerging nosocomial pathogen with multi-drug resistance. To the best of our knowledge, there is only one case report describing the computer tomography (CT) features of S. maltophilia pneumonia. In this article we will compare the features in the published case to those found in our patients. The importance of thoracic CT in febrile neutropenic patients will also be discussed.